2023
DOI: 10.3390/ijms24076126
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Post-Translational Modifications in Regulation of NLRP3 Inflammasome Activation

Abstract: Pathogen-associated molecular patterns (PAMPs) and danger-associated molecular patterns (DAMPs) induce NLRP3 inflammasome activation, and subsequent formation of active caspase-1 as well as the maturation of interleukin-1β (IL-1β) and gasdermin D (GSDMD), mediating the occurrence of pyroptosis and inflammation. Aberrant NLRP3 inflammasome activation causes a variety of diseases. Therefore, the NLRP3 inflammasome pathway is a target for prevention and treatment of relative diseases. Recent studies have suggeste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 146 publications
0
5
0
Order By: Relevance
“…Meanwhile, we also verified that hippocampal NLRP3 acetylation level was up‐regulated in Tauopathy transgenic mice and AD patients. It has been reported that PTMs of NLRP3 such as acetylation play a vital role in regulating NLRP3 inflammasome activation 39,40 . Therefore, these results stand for a hypothesis that NLRP3 inflammasome activation in Tauopathy transgenic mice and AD patients is mediated by NLRP3 acetylation, which is partly illustrated by the high correlation between NLRP3 acetylation level and IL‐1β or cleaved Caspase‐1 level.…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations
“…Meanwhile, we also verified that hippocampal NLRP3 acetylation level was up‐regulated in Tauopathy transgenic mice and AD patients. It has been reported that PTMs of NLRP3 such as acetylation play a vital role in regulating NLRP3 inflammasome activation 39,40 . Therefore, these results stand for a hypothesis that NLRP3 inflammasome activation in Tauopathy transgenic mice and AD patients is mediated by NLRP3 acetylation, which is partly illustrated by the high correlation between NLRP3 acetylation level and IL‐1β or cleaved Caspase‐1 level.…”
Section: Discussionmentioning
confidence: 74%
“…It has been reported that PTMs of NLRP3 such as acetylation play a vital role in regulating NLRP3 inflammasome activation. 39,40 Therefore, these results stand for a hypothesis that NLRP3 inflammasome activation in Tauopathy transgenic mice and AD patients is mediated by NLRP3 acetylation, which is partly illustrated by the high correlation between NLRP3 acetylation level and IL-1β or cleaved Caspase-1 level. Since Tau was identified as a bona fide acetyltransferase with enzymatic activity resides within the microtubule-binding regions, 43 it is thus reasonable to speculate that Tau protein may induce NLRP3 acetylation in Tauopathies.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…Acute occlusion of the coronary artery, oxidative stress, calcium overload, and adenosine triphosphate (ATP) overload occur when blood supply is restored after effective reperfusion measures Yang et al, 2018;Zhuang et al, 2023). The resulting cell debris and various inflammatory factors recognize pathogen-associated molecular patterns (PAMPs) or dangerassociated molecular patterns (DAMPs), recruiting adaptor proteins such as ASC containing a caspase-recruitment domain (ASC) and effector Caspase 1 to assemble the NLRP3 inflammasome (Xia et al, 2023;Zhan et al, 2022;. Caspase 1 undergoes self-cleavage into the enzymatically active cleaved Caspase 1, activating intracellular inflammatory responses (Hou et al, 2023).…”
Section: Discussionmentioning
confidence: 99%